EFEKTIVITAS PELAYANAN KESEHATAN PADA PUSKESMAS KECAMATAN PARANGLOE KABUPATEN GOWA - Hamrana, Hamrana; Mahsyar, Abdul; Sudarmi, Sudarmi (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThis study aims to determine the effectiveness of health services at the Puskesmas Parangloe District, Gowa Regency. This type of research is descriptive qualitative with data collection using observation, interview, and documentation techniques. Determination of informants using purposive sampling technique. The data validity technique used was source triangulation. The results showed that the quality of service can be said to be still not good. Good productivity from adequate medical equipment and health workers have good skills. The provision of incentives is fulfilled, it will be able to encourage the morale of health workers. The flexibility of adaptation that exists between the officer and the patient is considered to have met the needs. The supporting factors are the ability to work with noble motives, skills, time discipline, procedures and methods that have been determined and the inhibiting factor is the number of family members who are also present to accompany patients in emergencies, making it difficult for health care workers to treat patients. Keywords: Effectiveness, Service, Puskesmas